Enforcement of Criminal Laws Against Coal Mining Without a Permit in the Muara Enim Police Area - Purnomo; Saipuddin Zahri; Abdul Latif Mahfuz (Journal of Law, Politic and Humanities, 2024)
The development of mining activities without permits has also led to an increase in the trade of mining products on the black market, where natural resources are exploited illegally and mining products are distributed and sold illegally to avoid government taxes, which has reached a very worrying stage. This research method uses empirical juridical. Next, the topic of discussion was the enforcement of criminal law against coal mining without a permit in the Muara Enim police area. As a result, law enforcement carried out in the Muara Enim Police area against unlicensed miners has been carried out but has not been optimal, because there are no comprehensive regulations.